PERAN KEPEMIMPINAN KEPALA DESA DALAM PELAKSANAAN PEMBANGUNAN DI DESA SEJATI KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Indrian Syafitri; Lilis Suriani (UIR Press, 2019)
This research aims to determine the level of the role of Village head of's leadership in the implementation of Village development in sejati subdistricts of rambah hilir rokan hulu regency by the village head. Wherein, the role of leadership is measured by three indicators namely motivator, facilitator and mobilizer. The type of research that is located in Sejati of village subdistricts of Rambah Hilir Rokan Hulu Regency are descriptive survey, which to prioritize the list of the questionnaire as a data collected by the tool is then used as the main raw material for analyzing the empirical conditions of excistence obyectivitas research purposes with locations studied, and by using quantitative research methods. There are three groups of the population and sample in this research that the community totaling 21 people, village officials amounting to 8 people and village councils amounting 5 people. And the overall population and the sample as the sample where the village head is the key informan and sampling technique for village officials and village councils, while purposive sampling techniques to sejati village community. Type and data collection techniques used consist of primary data was collected by using questionnaires and interviews and secondary data was collected using observation. While the data analysis technique used is to use tools frequency table. This analysis technique based researchers assess and conclude that the role of Village head of's leadership in the implementation of Village development in Sejati is in the interval “act in accordance”, with the respondents and observations writer.